Partisipasi Politik Pemilih Pemula Pada Pemilihan Kepala Daerah Di Kabupaten Ciamis Tahun 2024 - Angga Nugraha; R.Rindu Garvera; Ii Sujai (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study is motivated by observations revealing the suboptimal political participation of first-time voters in the 2024 regional head elections (Pilkada) in Ciamis Regency. The problems identified include: (1) low participation among first-time voters, (2) limited access to political information for young voters, and (3) insufficient outreach and socialization efforts from the General Election Commission (KPU) regarding the 2024 Pilkada in Ciamis. This research employs a descriptive qualitative method. Primary data were collected through interviews with seven informants. Data collection techniques included literature studies, field observations, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that political participation among first-time voters remains limited when viewed through five influencing dimensions: modernization, changes in social class structures, the influence of intellectuals and modern mass communication, political elite conflicts, and extensive government involvement in social, economic, and cultural affairs. Key obstacles include limited digital literacy among young voters and their inability to distinguish credible information. Furthermore, many first-time voters lack understanding of candidates’ visions and missions. Efforts to overcome these challenges include encouraging first-time voters to be more selective with social media information and implementing political communication strategies tailored to the media habits of younger generations.